A Challenge for Engineering Biomimetic Microvascular Models: How do we Incorporate the Physiology? - Lampejo, Arinola O.; Hu, Nien-Wen; Lucas, Daniela; Lomel, Banks M.; Nguyen, Christian M.; Dominguez, Carmen C.; Ren, Bing; Huang, Yong; Murfee, Walter L. (Frontiers in Bioengineering and Biotechnology, 2022)
The gap between in vitro and in vivo assays has inspired biomimetic model development. Tissue engineered models that attempt to mimic the complexity of microvascular networks have emerged as tools for investigating cell-cell and cell-environment interactions that may be not easily viewed in vivo. A key challenge in model development, however, is determining how to recreate the multi-cell/system functional complexity of a real network environment that integrates endothelial cells, smooth muscle cells, vascular pericytes, lymphatics, nerves, fluid flow, extracellular matrix, and inflammatory cells. The objective of this mini-review is to overview the recent evolution of popular biomimetic modeling approaches for investigating microvascular dynamics. A specific focus will highlight the engineering design requirements needed to match physiological function and the potential for top-down tissue culture methods that maintain complexity. Overall, examples of physiological validation, basic science discoveries, and therapeutic evaluation studies will emphasize the value of tissue culture models and biomimetic model development approaches that fill the gap between in vitro and in vivo assays and guide how vascular biologists and physiologists might think about the microcirculation.